2016
DOI: 10.1501/vetfak_0000002749
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of Staphylococcus aureus strains isolated from beef, sheep and chicken meat

Abstract: Summary:The objective of this study was to evaluate the occurrence, enterotoxigenic properties and antibiotic resistance of Staphylococcus aureus in beef, sheep and chicken meat. For this purpose, 225 meat samples were obtained from different supermarkets in Ankara. Firstly, these samples were analysed phenotypically for coagulase-positive staphylococci and S. aureus. Then phenotypically determined S. aureus isolates were confirmed through PCR assay and investigated by multiplex PCR for enterotoxin genes and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…A study of 40 beef samples in Pakistan showed the presence of Staphylococcus aureus in 75% of the samples and 63% identified resistance to cefoxitin, a marker of MRSA (Sadi et al 2020). Similar data on the prevalence of Staphylococcus aureus in 14.6% beef samples in Turkey were reported by Özdemir and Keyvan (2016). Cefoxitin resistance was found in 22.8% of them.…”
Section: Prevalence Of Mrsa In Foodsupporting
confidence: 85%
See 3 more Smart Citations
“…A study of 40 beef samples in Pakistan showed the presence of Staphylococcus aureus in 75% of the samples and 63% identified resistance to cefoxitin, a marker of MRSA (Sadi et al 2020). Similar data on the prevalence of Staphylococcus aureus in 14.6% beef samples in Turkey were reported by Özdemir and Keyvan (2016). Cefoxitin resistance was found in 22.8% of them.…”
Section: Prevalence Of Mrsa In Foodsupporting
confidence: 85%
“…Most authors found high resistance to penicillin and ampicillin (up to 100%). The data by erythromycin and tetracycline resistance are similar (Jackson et al 2013;Kim et al 2020;Mahros et al 2021;Özdemir and Keyvan 2016;Wu et al 2019). Antibiotic susceptibility testing showed that most of MRSA isolates from meat samples in Denmark were resistant to erythromycin (95%), tetracycline (84%), and clindamycin (79%), and some were resistant to ciprofloxacin (32%).…”
Section: Antimicrobial Resistance Of Mrsa In Foodsupporting
confidence: 59%
See 2 more Smart Citations